A differences the effectiveness of muscle energy technique and eccentric exercise on ultrasound intervention to reduce disability in tennis elbow patients - Ni Luh Nopi Andayani; Ari Wibawa; Gede Parta Kinandana (MEDIA ILMU KESEHATAN, 2022)
Background: Humans in their daily life cannot be separated from activities that involve hands, both in activities and work. One of the musculoskeletal problems that can occur is Tennis Elbow is a painful feeling on the outside of the elbow associated with excessive wrist extensionObjective: The purpose of this study was to determine the differences in the effectiveness of muscle energy technique and eccentric exercise on ultrasound intervention in reducing disability in tennis elbow patientsMethods: Experimental research method with pre-test and post-test two group design.The study was conducted in private physiotherapy in Denpasar and Badung. There were 32 samples divided into group I (ultrasound and muscle energy technique) and group II (ultrasound and eccentric exercise)Results: Wilcoxon Test was each group p <0.05, there is a decrease disability on tennis elbow patients in each group. The difference test between groups was carried out using the Mann Whitney U Test, p <0.05, there is a significant difference between group 1 and 2Conclusion: there are differences in the effectiveness of muscle energy technique and eccentric exercise on ultrasound intervention to reduce disability in tennis elbow patients